Sleep patterns and nocturnal cardiac autonomic activity in female athletes are affected by the timing of exercise and match location - Costa, J. A.; Brito, J.; Nakamura, F. Y.; Figueiredo, P.; Oliveira, E.; Rebelo, A. (Chronobiology International, 2019)
The aim of the current study was to analyze the influence of the timing of training and matches, and match location, on sleep pattern and nocturnal cardiac autonomic activity in female soccer players. A total of 17 female soccer players (age: 21.6 ± 2.3 years; mean ± SD) wore wrist actigraph units and heart rate (HR) monitors during night-sleep throughout 18 night-training days (NTD), 18 resting days (RD), and 6 match-days (MD; 3 away-matches [AM] and 3 home-matches [HM]) of the competitive period. Training load was quantified by session rating of perceived exertion (sRPE), heart rate (HR), training impulse (TRIMP), and subjective well-being. In NTD, sleep onset time and total sleep time were significantly impaired compared to MD (+ 1:47 [0:48; 1:55] hours and -1:35 [-1:42; -0:57] hours, respectively; p< 0.001; mean difference ± 95% confidence interval [CI]) and RD (+ 1:31 [0:52; 1:49] hours and -1:26 [-1:28; -0:55] hours, respectively; p< 0.001). In AM, sleep onset time was delayed compared to HM (+ 0:36 [0:12; 0:44] hours; p< 0.001). Sleep latency was higher in NTD compared to RD (+ 4 [2; 5] min; p< 0.001), as well as after AM compared to HM (+ 5 [1; 7] min; p< 0.001). HR during sleep was significantly increased after NTD and MD compared to RD (+ 4 [1; 5] b.p.m and + 3 [1; 4] b.p.m, respectively; p< 0.001). Furthermore, HR variability decreased after NTD and MD compared to RD (e.g., lnRMSSD, -0.09 [-0.18; -0.08] ln[ms] and -0.17 [-0.27; -0.11] ln[ms], respectively; p< 0.001). Overall, the time of day for soccer practice (i.e., training at night) and match location (i.e., away matches) may cause disruption in sleep patterns and/or in autonomic cardiac activity in female soccer players. Additionally, playing official matches during the day and training at night may affect nocturnal cardiac autonomic activity by decreasing vagal-related modulation and increasing HR during sleep.